Nasal sill augmentation: an overlooked concept in rhinoplasty-a technical note and review of the literatures - Gholamhossein Adham; Seied Omid Keyhan; Hamid Reza Fallahi; Heliya Ziaei; Mohan Thomas (SpringerOpen, 2021)
Abstract Background Nasal sill is one of the components of the alar ring, affecting the esthetic outcomes of rhinoplasty; accordingly, we developed a novel technique to adjust defects in this area and compared it with the available techniques. Methods Our technique was based on creating a tunnel access to the nasal sill area through an incision made in the lower third of the columella using the open approach or through a nostril base incision in patients, who underwent alar base reduction, followed by insertion of a cartilaginous graft into the marked defect area. Results A total number of 54 patients with a defect in the nasal sill area were included in this study. Thirty-one patients underwent open rhinoplasty with the sill approach from the lower third of the columella, while 23 patients underwent rhinoplasty with a nostril base approach for nasal sill augmentation procedure. There were no reports of patient dissatisfaction, infection, bleeding, sensory dysfunction, or remaining asymmetry of the sill area. Conclusion Based on the findings of the present study, this technique can be successfully used in reconstructing the nasal sill area with minimal complications and morbidity.